Being watched : Yvonne Rainer and the 1960s - Lambert-Beatty, Carrie (Cambridge : MIT press, 2008)
Judson Dance Theater in Hindsight -- ##Sections and chunks: serial time -- ##Mediating Trio A -- ##Other solutions -- ##Performance demonstration -- ##Conclusion: Taking sides.
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Rainer, Yvonne